(untitled) (De Musica, 2021)
The record could almost seem incongruous in the contemporary European musical world where dematerialization reigns, especially with the significant increase in streaming. However, besides the digital offer, where there are very disparate formats of qualities and where the importance of nomadism sometimes overrides the sound quality, it is clear that the record survives in the form of CD or even vinyl. In addition to the battle between analogic and digital fans who criticize its superiority, if the record remains a “calling card” for artists (sometimes founding their own record label to escape the dictates of the big majors) and a “noble” medium for listeners, it is because extra-musical elements are to be considered to explain this survival: the sometimes luxurious object that the record constitutes becomes indeed a benchmark in a society where novelty and profusion have taken a preponderant place. Listening to a record remains a privileged moment when, at the ear, combine the pleasure of the eye and a sense of ownership of an object chosen also for its aesthetics and for what it symbolizes in the middle of the overabundant offer from the web.